Know Your Road Sign for kids : Development of Road Sign Learning Application Using VARK Learning Model - Sharifah Nurmaisarah Afiqah Syed Abdullah; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2024)
Ignorance of traffic signs is a frequent cause of car accidents. Therefore, it is important to train kids about traffic signs, in order to grow a responsible driver. Traffic signs, also known as road signs, are signs that are placed alongside or above roads to provide instructions or information to drivers. This learning application will teach kids the basic of road signs via VARK learning model. VARK stands for visual, auditory, reading, and kinesthetic learning. VARK elements used in this application are visual, reading, and audio. The objectives of this project are to teach kids about road signs. MMCD was used in order to develop this application. The target user for this application is 7 to 9 years old kids. User analysis was done by interviewing subject matter experts. This application was developed in Unity and was expected to be able to help elementary school teachers teach basic road signs.